Remediation of cadmium-contaminated wheat soil with cow dung: interactions between soil chemical properties, microbial communities, functional genes, and heavy metal bioavailability - Liu, Getong; Han, Ziyu; Sun, Jiajun; Liu, Chenfeng; Shi, Huading; Fei, Yang; Liang, Jiahui; Mu, Yunsong; Wang, Hongjie; Zhang, Rong (Frontiers in Environmental Science, 2025)
Cow dung reduces the bioavailability of heavy metals (HMs) in wheat soils. However, interactive influence of soil chemical properties, microbial communities and functional genes in HM immobilization need to be further investigated. Therefore, the effects of cow dung on heavy metals content in soil and wheat, soil microbial community structure, and heavy metal resistance genes (MRGs) were tested with pot experiment. Cow dung reduced the bioavailable forms of Cd by 8% to 21%, thereby reducing the Cd content of wheat grains by 30.5% to 46.1%. Bioavailable forms of Cd in soil were significantly and negatively correlated with soil chemical properties, relative abundance of microbial genera (such as Bradyrhizobium spp. and Mycolicibacterium spp.), and relative abundance of MRGs (such as actA and fpvA). Concurrently, the bioavailable forms of Cu and Zn exhibited significant correlations with Shannon index and MRGs (such as copC). These results indicated that changes in soil environmental factors (soil chemical properties, microbial communities and MRGs) are conducive to reducing the bioavailability of Cd. However, the high levels of Cu and Zn in cow dung may also disrupt soil ecology, resulting in a decline in microbial diversity and impacting the abundance of MRGs. Therefore, the rates of application of cow dung should be carefully selected and should not exceed 2.5% (w/w). These results may provide scientific evidence for the safe use of cow dung and remediation of heavy metals in wheat soils.